Investigation into damaged gear of off-road motorcycles - Bublikova, Dagmar; Jirkova, Hana; Rubesova, Katerina; Bunda, Zbynek (Manufacturing Technology Journal, 2020)
If failure occurs in gear wheels in a racer motorcycle gearbox, the possible causes are manifold: inadequate material, improper care (poor lubrication, incorrect assembly) or inadequate thermochemical treatment procedure. This investigation focused on spur wheels of chromium-nickel Czech Standard (CSN) 16720 steel containing 0.18 % C, 0.4 % Mn, 1.5 % Cr, 4.25 % Ni and 1 % W. The steel had been quenched to 60-62 HRC and the case hardening depth was 0.8 mm. The client requested that these wheels have a life of 100 hours. The failure occurred while the wheels were in operation. The fracture surfaces in the wheels were examined in a scanning electron microscope (SEM). The fracture surfaces were prominent in the failure locations. EDS point analysis in the SEM revealed spots with higher chromium levels on the fracture surfaces. The average size of these spots was several dozen micrometres. The spots were suspected to have caused or contributed to the failure. A hardness profile across one tooth was measured using a microhardness tester. In addition, the thickness of the carburized layer was determined. Quality of the surface was assessed using macrophoto-graphs taken with a low-power stereomicroscope. In addition, metallographic sections were prepared and observed in a scanning electron microscope (SEM) and light microscope.
Keywords: Q&P process; retained austenite; AHSS steels; X-ray diffraction; thermomechanical simulator